ChemInform Abstract: Selectivity Control by Silver Catalysts in the Cycloisomerization of 1, 6‐Enynes Derived from Propiolamides. Issue 23 (16th May 2013) - Koo, Jaeyoung; Park, Hyun‐Sub; Shin, Seunghoon
Abstract Ag(I)‐catalyzed title reactions result in selective formation of Alder‐ene type 1, 4‐dienes.